What Is Teamwork? A Mixed Methods Study on the Perception of Teamwork in a Specialized Neonatal Resuscitation Team - Ediger, Krystyna; Rashid, Marghalara; Law, Brenda Hiu Yan (Frontiers in Pediatrics, 2022)
Introduction: Neonatal resuscitation is a team-based activity involving many decisions and tasks. Non-technical factors, such as teamwork, are increasingly recognized as impacting how well neonatal resuscitation performance, and therefore influencing infant outcomes. Prior studies on teamwork in neonatal resuscitation have focused on quantification of teamwork behaviors, or the effects of team training. This study aimed to explore healthcare providers’ own perception of teamwork in this specialized environment to identify perceived barriers and facilitators to effective team functioning. Methods: This single-center exploratory sequential mixed methods study used two phases. First, semi-structured interviews were conducted, and thematic analysis used to identify themes. Subsequently, interview data informed the development of quantitative surveys to explore selected themes in the wider team. Results: From ten semi-structured interviews, seven themes were identified including: 1) Team Composition, 2) Effective Communication, 3) Team leadership, 4) Hierarchy, 5) Team Training, 6) Debriefing, and 7) Physical Environment. Perceived teamwork facilitators include role assignment, familiarity, team composition, talking out loud to maintain shared mental models, leadership, and team training. Perceived barriers included time pressures, ad hoc team, ineffective leadership, and space limitations. Selected themes (Communication, Speaking up, Hierarchy, and Leadership) were further explored via electronic surveys distributed via email to all members of the resuscitation team. There were 105 responses; a response rate of ~53%. All respondents agreed or strongly agreed that speaking up is important; however, not all felt comfortable doing so. Neonatal fellows (14%) and nurses (12%) were most likely to report not feeling comfortable speaking up. All respondents agreed that team communication is important to an effective resuscitation. Most respondents (91.5%) agreed that a hierarchy exists within the team; 54.3% believed that hierarchy positively contributes to effective resuscitation. All respondents agreed or strongly agreed that having a clearly defined leader is important in delivery room resuscitations. Ineffective leadership was the most cited reason for poor team communication. Conclusions: In this mixed methods study of perceptions of teamwork within a specialized, multi-disciplinary neonatal resuscitation team, communication, hierarchy, and leadership were positively perceived and facilitates teamwork. However, even in this environment, some nurses and trainees expressed discomfort with speaking up.